IoT-based implementation of classroom response system for deaf and mute using MQTT protocol. (18th February 2020) - Mishra, Manasi; Reddy, S.R.N.
Speaking and hearing plays an important role in effective teaching, individuals who lack these abilities faces an uphill battle. Quantum of researches has focused on designing various approaches to teach deaf and mute students. However, assessing whether students are following the course materials by creating an active learning environment is very difficult in this context. Integrating IoT technologies into their classroom can add an immense value in this area by providing interactive low-cost solution which can solve the purpose and also improve the quality and efficiency of the education system thereby making education more appealing than ever before. This paper presents the review and case study of various existing solutions and design and development of one such system using low cost hardware and MQTT lightweight protocol for efficient device to device communication to encourage active learning environment in the classroom without much modifications in the existing academic infrastructure.